The anterior intercostal artery perforator flap in immediate oncoplastic breast reconstruction: current applications and future perspectives - Kong, Weijie; Wang, Zhiyao; Liu, Yang; Pei, Jie; Guo, Fan (Frontiers in Oncology, 2026)
In recent years, the anterior intercostal artery perforator (AICAP) flap has gained increasing attention for its minimal donor-site morbidity, natural contour, and excellent scar concealment. This review begins by outlining the vascular anatomy of the anterior intercostal perforators, including their distribution, perfusion characteristics, and key considerations for preoperative imaging. We then summarize the indications and limitations of other commonly used chest wall perforator flaps, such as the lateral intercostal artery perforator (LICAP) and thoracodorsal artery perforator (TDAP) flaps to contextualize the unique role of AICAP in partial breast reconstruction. Building on this foundation, we focus on the surgical design, harvest dimensions, arc of rotation, and anatomical relationship between AICAP flaps and the inframammary fold. Compared with traditional local flaps, AICAP flaps offer reliable vascularity, excellent tissue compliance, minimal donor-site disruption, and low rates of postoperative complications. Their location within a natural skin crease also allows the resulting scar to remain well concealed. These features make AICAP particularly suitable for precise reconstruction of defects in the lower and lower-inner breast quadrants, where long-term aesthetic stability is often difficult to achieve. Nonetheless, standardized indications, anatomical variability, limited sample sizes, and a lack of long-term follow-up continue to constrain the strength of current evidence. Overall, this review synthesizes the anatomical basis, technical considerations, clinical advantages, and existing limitations of the AICAP flap. We further highlight emerging directions—including image-guided perforator mapping, personalized flap design, and long-term outcome assessment—to support the development of more standardized and reproducible clinical pathways for AICAP-based breast reconstruction.